函数y=sinx(cosx+1)的导函数

来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 21:30:35
函数y=sinx(cosx+1)的导函数函数y=sinx(cosx+1)的导函数函数y=sinx(cosx+1)的导函数y''=cosx(cosx+1)+sinx(-sinx)=cos2x+coxy=s

函数y=sinx(cosx+1)的导函数
函数y=sinx(cosx+1)的导函数

函数y=sinx(cosx+1)的导函数
y'=cosx(cosx+1)+sinx(-sinx)=cos2x+cox

y=sinx(cosx+1)
y'=[sinx(cosx+1)]'=(sinx)'*(cosx+1)+sinx*(cosx+1)'=cosx*(cosx+1)-(sinx)^2=cosx+(cos^2x-sin^2x)
=cosx+cos2x

y=sinx*cosx+sinx
y'=cosx*cosx-sinx*sinx+cosx
y'=cos2x+cosx

y'=cosx(cosx+1)-sin^2x

y'=(sinx)'*(cosx+1)+(sinx)*(cosx+1)'
=(cosx)*(cosx+1)+(sinx)*(-sinx)
=cos2x+cosx